2002
DOI: 10.1080/09541440143000050
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the time course of multidimensional stimulus discrimination: Analyses of viewing patterns and processing times during “same”-“different“ decisions

Abstract: We investigated the time course of conjunctive ''same''-''different'' judgements for visually presented object pairs by means of combined reaction time and on-line eye movement measurements. The analyses of viewing patterns, viewing times, and reaction times showed that participants engaged in a parallel self-terminating search for differences. In addition, the results obtained for objects differing in only one dimension suggest that processing times may depend on the relative codability of the stimulus dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(118 citation statements)
references
References 73 publications
9
107
2
Order By: Relevance
“…Brought to you by | Radboud University Nijmegen Authenticated Download Date | 3/3/15 2:47 PM Specific results in Table 1 are consistent with conclusions reported by Viethen and Dale (2008) and Belke and Meyer (2002). Viethen and Dale report on research that focuses on Natural Language Generation algorithm development.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Brought to you by | Radboud University Nijmegen Authenticated Download Date | 3/3/15 2:47 PM Specific results in Table 1 are consistent with conclusions reported by Viethen and Dale (2008) and Belke and Meyer (2002). Viethen and Dale report on research that focuses on Natural Language Generation algorithm development.…”
Section: Discussionsupporting
confidence: 80%
“…They observed spatial overspecification in 231 (36.6%) of a total of 630 descriptions elicited in a web-based production experiment; participants mentioned location information although this was never necessary for the identification of the object. Belke and Meyer (2002) found in a naming experiment that color was overspecified substantially more often than size. Also, when participants had the choice of including either size or color to build a minimally specified expression, color was specified more often than size (68.1 percent, 128 utterances versus 9 percent, 17 utterances); the remaining utterances (22.9 percent, 43 utterances) were overspecified (both the size and the color were specified).…”
Section: Discussionmentioning
confidence: 99%
“…Pechmann (1994) found that color was earlier available than size in a referential communication task. In production, Belke and Meyer (2002) and Belke (2006) found that overspecifications of color were more pervasive than overspecifications of size.…”
Section: Minimal Expression Containing Only Location Information -Addmentioning
confidence: 99%
“…Many algorithms [26,34] give priority to properties, not based on discriminatory power, but on how salient, relevant or preferred they are. This notion of preference is usually defined by appealing to psycholinguistic findings, for example, the finding that speakers tend to avoid prototypically gradable properties such as size, unless they are absolutely required, in contrast for example to colour which, as we have seen, is used very frequently [35,36]. However, many such findings are based on experimental domains in which colours are maximally salient and distinct.…”
Section: Salience and Contextual Knowledgementioning
confidence: 93%